Executive functioning moderates neural reward processing in youth - Kryza-Lacombe, Maria (Cogn Affect Behav Neurosci, 2020)
Although executive functioning has traditionally been studied in “cool” settings removed from emotional contexts, it is highly relevant in “hot” emotionally salient settings such as reward processing. Furthermore, brain structures related to “cool” executive functioning and “hot” reward-related processes develop simultaneously, yet little is known about how executive functioning modulates neural processes related to reward processing during adolescence, a period of time when these systems are still developing. The present study examined how performance on “cool” behavioral executive functioning measures moderates neural reward processing. Youths (N=43, mean age[SD]=13.74[1.81] years,) completed a child-friendly monetary incentive delay task during fMRI acquisition that captures neural responses to reward anticipation and to reward receipt and omission. Performance on inhibitory control and cognitive flexibility measures, captured outside the scanner, was used to predict brain activation and seed-based connectivity (ventral striatum and amygdala). Across analyses, we found that executive functioning moderated youths’ neural responses during both reward anticipation and performance feedback, predominantly with respect to amygdala connectivity with prefrontal/frontal and temporal structures, supporting previous theoretical models of brain development during adolescence. Overall, youths with worse executive functioning had more pronounced differences in neural activation and connectivity between task conditions compared to youths with better executive functioning. This study contributes to elucidating the relationship between “cool” and “hot” processes and our findings demonstrate that simple executive functioning skills moderate more complex processes that involve incorporation of numerous skills in an emotionally salient context, such as reward processing.